Shelf-life extension of chilled and superchilled dark-cutting beef held under combined anoxic master packaging and high-oxygen packaging both enriched with carbon dioxide. (December 2022) - Yang, Xiaoyin; Xu, Baochen; Zhang, Xiran; Luo, Xin; Zhang, Yimin; Mao, Yanwei; Liang, Rongrong
Abstract: The microbiological and quality attributes of dark-cutting (DC) beef were assessed during chilled and superchilled anoxic packaging storage (80% CO2 MP: 80% CO2 /20% N2 ; 40% CO2 MP: 40% CO2 /60% N2 ; VP: vacuum packaging) followed by a chilled high-oxygen packaging display period (HiOx-MAP: 60% O2 /40% CO2 ). During storage, both MP steaks showed lower ( P  < 0.05) purge loss and pH than VP steaks, and superchilling significantly suppressed lipid oxidation. The following HiOx-MAP produced a bright red color in all steaks during display, and MP storage rendered displayed steaks higher ( P  < 0.05) redness values than VP storage. Both superchilled MP-HiOx systems exerted the best preservation for DC beef with lower bacterial counts and TVB-N values among the packaging types, in which the display-life was prolonged to 14 days after 21-days storage. Despite the levels of CO2 influenced microbiota dynamics during anoxic storage, Carnobacterium finally became the predominant bacteria under HiOx-MAP. Highlights: Shelf-life of DC beef in CO2 -enriched anoxic packaging and HiOx-MAP was explored. Superchilled 80% CO2 and 40% CO2 MP-HiOx systems had the best antibacterial effect. HiOx-MAP (60% O2 /40% CO2 ) significantly improved the color of DC beef. Carnobacterium was predominant in HiOx-MAP after a long-term anoxic storage.